2015
DOI: 10.1684/epd.2015.0773
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal eyelid movements in patients with visual‐sensitive reflex seizures

Abstract: Aim. Paroxysmal eyelid movements (PEM) are non‐epileptic episodes characterized by eyelid closure, upturning of the eyes, and rapid eyelid flutter. The aim of this study was to report clinical and EEG data of patients with PEM and its relationship with visual sensitivity. Methods. We studied 26 patients with epilepsy (12 males and 14 females; mean age: 14.0±6.9 years) who presented PEM. The epilepsy was idiopathic generalized (eight cases), idiopathic focal (six cases), symptomatic focal (five cases), and refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These episodes do not present any EEG abnormalities and are not triggered by hyperventilation or photic stimulation ( 11 ). A coexistence of PEM, photoparoxysmal EEG responses, increased blinking and epileptic eyelid myoclonia have been already reported, suggesting an underlying dysfunction involving cortical-subcortical neural networks and a possible genetic relationship between PEM and epilepsy ( 12 ).…”
Section: Discussionmentioning
confidence: 97%
“…These episodes do not present any EEG abnormalities and are not triggered by hyperventilation or photic stimulation ( 11 ). A coexistence of PEM, photoparoxysmal EEG responses, increased blinking and epileptic eyelid myoclonia have been already reported, suggesting an underlying dysfunction involving cortical-subcortical neural networks and a possible genetic relationship between PEM and epilepsy ( 12 ).…”
Section: Discussionmentioning
confidence: 97%
“…Each frequency was tested by separate trains of flashes with an inter-stimulus free period of five seconds, during both conditions eye closed and eyes open. Pattern sensitivity was tested by a standard procedure of stimulation, according to recommended guidelines (Wilkins et al, 2005), as reported elsewhere (Brinciotti et al, 2015). Briefly, we used three types of black-and-white full-field pattern (checks, horizontal stripes, vertical stripes), two black-and-white hemi-field pattern (left and right, Stimulus were presented in reversal mode (1.6 Hz) to ensure a constant total luminance, and any reversal was synchronized with a digital marker to carry out subsequent off-line analysis of the signal.…”
Section: Recording Methodsmentioning
confidence: 99%
“…Underwritten informed consent, all members underwent clinical, EEG, neuro-imaging and laboratory evaluations based on specific clinical indications for each subject. Video-EEG monitoring was recorded in each member at rest and during standardized visual stimuli with intermittent light stimulation (ILS), pattern stimulation (PS) and watching television, according to a protocol used in our center [9] . Genomic DNA of each member was extracted from peripheral blood with standard procedures and analyzed by single nucleotide polymorphism microarray-based analysis (SNP-array Cytoscan; Affymetrix, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%